Cultural intelligence, values and motivation to learn in Argentinean cadets - Depaula, Pablo Domingo (2012)
The aim of this study was to analyze if relations among cultural intelligence levels, motivation to academic learning and human values on the working area in a sample of 400 argentine military students, cadets becoming officials on Argentine Army (377 men and 23 women), originating of diverse argentine provinces. Bivaried analyses of correlation through coefficient r of Pearson were made. Results show that students present tie values to the care of the national traditions, and at the same time the value “stimulation” is associated to the creative resolution of new experiences on uncertain situations, balancing their autorestriction that would limit the opening towards cultural diversity.